2022
DOI: 10.1038/s41598-022-04780-4
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of endogenous α-synuclein induced by extracellular seeds initiates at the pre-synaptic region and spreads to the cell body

Abstract: Accumulation of phosphorylated α-synuclein aggregates has been implicated in several diseases, such as Parkinson's disease (PD) and dementia with Lewy bodies (DLB), and is thought to spread in a prion-like manner. Elucidating the mechanisms of prion-like transmission of α-synuclein is important for the development of therapies for these diseases, but little is known about the details. Here, we injected α-synuclein fibrils into the brains of wild-type mice and examined the early phase of the induction of phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…It remains to be clarified whether in patients with PD, α-syn is highly expressed or has impaired degradation, and which metabolic dysfunctions lead to abnormal α-syn phosphorylation. It is well known that these aberrant changes of α-syn represent predisposing conditions for generating pathologic α-syn aggregates [ 32 ]. However, the phospho-α-syn deposition detected in the OM of PD patients should be further analyzed in a larger number of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be clarified whether in patients with PD, α-syn is highly expressed or has impaired degradation, and which metabolic dysfunctions lead to abnormal α-syn phosphorylation. It is well known that these aberrant changes of α-syn represent predisposing conditions for generating pathologic α-syn aggregates [ 32 ]. However, the phospho-α-syn deposition detected in the OM of PD patients should be further analyzed in a larger number of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This difference with the in vitro situation in which many "pure" NIIs are observed after seeding with 1B might be due to the fact that in vitro, every neuronal soma is directly exposed to 1B seeds, increasing the probability that exogenous fibrils quickly reach the nucleus after uptake and seed there the buildup of a "pure" NII. In vivo, the synucleinopathic neurons observed are distant from the 1B fibril injection site (especially the entorhinal cortex neurons in Figure 10), and the inclusions observed in their somas derive from the intraneuronal retrograde spread of an aggregative process initiated distally in their pre-synaptic terminals [77]. In this case, it seems likely that NCIs are formed first, with α-Syn fibril fragments secondarily leaking out from the NCI and reaching the intranuclear space to seed NIIs.…”
Section: α-Syn Niis Seeded In Vivo In Mice After Stereotaxic Injectio...mentioning
confidence: 99%
“…Although α-syn PFF pathology is proposed to be initiated from axons (14,(57)(58)(59), little is known about presynaptic molecules that bind to α-syn PFFs. Previous studies have identified several α-syn PFF-binding membrane proteins such as PrP c , LAG-3 and FcγRIIB (47)(48)(49)(60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, α-syn can be released from one neuron and taken up by other neurons, resulting in spreading of α-syn pathology in the brain (6)(7)(8)(9). Evidence regarding trans-synaptic transmission of pathological αsyn (10)(11)(12)(13)(14) suggests that synaptic adhesion and/or transmission mechanisms are involved in α-syn pathology but the specific molecular mechanisms of this require further investigation. Synapse formation, maturation, maintenance, and plasticity are regulated by a series of neuronal adhesion molecules that form "synaptic organizing complexes" (15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%